La smaterializzazione della giustizia e la demolizione del rituale del processo (Società e diritti, 2021)
AbstractDuring the Covid-19 pandemic, health problems led to the adoption of emergency rules for the exercise of "remote" judicial activity, with digital and technological tools. The civil trial was thus "dematerialized" and some of the rules introduced for the emergency now seem to be about to become permanent. It is possible to frame this choice of legislative policy in terms of demolishing the ritual structure of the trial. The attack on the judicial ritual is, on the one hand, functional to the progressive assimilation of the process to alternative dispute resolution (ADR). Furthermore, the demolition of the ritual through digitalization leads to an emptying of the process from within, an elimination of its symbols, of the founding myths of power and state auctoritas. By demolishing the rite, the process falls as a means of protecting rights. But it falls because the foundation of state power is under attack.